Ладошкины сказки: художественная лит-ра / Анна Никольская ; художник Анна Юдина - Никольская Анна Олеговна (Издательский Дом Мещерякова, 2013)
Экземпляры: ДБ (20140602) / Инвентарный номер: 45830 / Цена: 387.53 / Авт.знак: Н 64 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6